The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1063/1.1137365
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the quantum efficiency of microchannel plate detectors: The collection of photoelectrons from the interchannel web using an electric field

Abstract: We report dependence of the extreme ultraviolet quantum efficiency (QE) of a microchannel plate (MCP) detector upon the electric field strength above its input face. Using an uncoated plate, we measured increases up to 80% as the field was raised from 0 V/μ to between 0.01 and 0.1 V/μ. Further increases in electric field resulted in a monotonic decrease in QE. Detector spatial resolution was found to degrade for these small field values but could be recovered, while maintaining most of the QE increase, by oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The OPoSAP has a spatial resolution of approximately 0.25mm, and no degradation has been observed with grid bias as low as 15V. A more detailed analysis of the trajectory of photoelectrons has been performed by Taylor et al [9], who considered the effect on detector resolution in a UV imaging system, and their results were similar to those given here. Mass-to charge The grid potentials given in each case are quoted with respect to the front face of the MCP, which was set to -50V.…”
Section: Effect On Timing and Spatial Resolutionsupporting
confidence: 66%
See 1 more Smart Citation
“…The OPoSAP has a spatial resolution of approximately 0.25mm, and no degradation has been observed with grid bias as low as 15V. A more detailed analysis of the trajectory of photoelectrons has been performed by Taylor et al [9], who considered the effect on detector resolution in a UV imaging system, and their results were similar to those given here. Mass-to charge The grid potentials given in each case are quoted with respect to the front face of the MCP, which was set to -50V.…”
Section: Effect On Timing and Spatial Resolutionsupporting
confidence: 66%
“…Taylor et al [9] observed a drop off in the detection efficiency for incident photons at large grid bias, when the photoelectrons generated from the interchannel web failed to reach the nearest channel, and are returned instead to the web. However, this effect was only appreciable for larger applied fields than are applied here (up 1000V/mm), or for lower energy photoelectrons.…”
Section: Cs-302mentioning
confidence: 99%
“…36 Measurements on other microchannel plates yield collection efficiencies of about 90%, even for electron energies as low as 100 eV. 37 On scales of 10 |i to 1 mm, the collection efficiency varies less than 1% (consistent with statistical fluctuations in the measurement) over the area of the microchannel plate. 38,39 There are variations of 5% to 10% over scales larger than 5 mm.…”
Section: Collection E'n^'encymentioning
confidence: 93%
“…They were covered with nearly transparent grids, which had negative voltage relative to the MCP front surfaces to maximize the detection efficiency [47,48]. The MCP for the projectile detection had a delay line anode to generate a position signal.…”
Section: Methodsmentioning
confidence: 99%